Prevalence of hypodontia of permanent teeth in children visiting a university hospital in Chennai- a retrospective study. - GUNASEKARAN, GOKUL; MANI, GEO; RENGALAKSHMI, SRI (The journal of contemporary issues in business and government, 2020)
Hypodontia is one of the most common dental anomalies encountered in the normal dental practices which is a major cause for malocclusion among growing teens and requires replacement in adults. Hypodontia occurs due to congenitally missing teeth and are not found in radiographs. Early diagnosis would help to determine the eruption pattern of the other teeth and help in treatment planning.The aim of this study was to evaluate the prevalence of hypodontia of permanent teeth in the Chennai population. In this retrospective study design, patient case reports were evaluated, of which 6682 patient case sheets which matched the inclusion criteria were selected for evaluation for congenitally missing teeth and the treatment performed for each case with congenitally missing teeth was evaluated. The data was then tabulated and analysed in SPSS software. Descriptive statistics and Chi square tests were performed. The total percentage of study population with congenitally missing teeth was 0.64%. Mandibular incisors were the most common congenitally missing teeth.The prevalence of congenitally missing permanent teeth in the Chennai population was found to be 0.64% .